[18F]-(2S,4R)4-Fluoroglutamine PET Imaging of Glutamine Metabolism in Murine Models of Hepatocellular Carcinoma (HCC) - Youngho Seo; Miranda C. Craig; Stephanie T. Murphy; Jinjin Feng; Xin Chen; Mariia Yuneva (Molecular Imaging)
Purpose. Quantitative in vivo [18F]-(2S,4R)4-fluoroglutamine ([18F]4-FGln or more simply [18F]FGln) metabolic kinetic parameters are compared with activity levels of glutamine metabolism in different types of hepatocellular carcinoma (HCC). Methods. For this study, we used two transgenic mouse models of HCC induced by protooncogenes, MYC, and MET. Biochemical data have shown that tumors induced by MYC have increased levels of glutamine metabolism compared to those induced by MET. One-hour dynamic [18F]FGln PET data were acquired and reconstructed for fasted MYC mice (n=11 tumors from 7 animals), fasted MET mice (n=8 tumors from 6 animals), fasted FVBN controls (n=8 normal liver regions from 6 animals), nonfasted MYC mice (n=16 tumors from 6 animals), and nonfasted FVBN controls (n=8 normal liver regions from 3 animals). The influx rate constants (K1) using the one-tissue compartment model were derived for each tumor with the left ventricular blood pool input function. Results. Influx rate constants were significantly higher for MYC tumors (K1=0.374±0.133) than for MET tumors (K1=0.141±0.058) under fasting conditions (P=0.0002). Rate constants were also significantly lower for MET tumors (K1=0.141±0.135) than normal livers (K1=0.332±0.179) under fasting conditions (P=0.0123). Fasting conditions tested for MYC tumors and normal livers did not result in any significant difference with P values > 0.005. Conclusion. Higher influx rate constants corresponded to elevated levels of glutamine metabolism as determined by biochemical assays. The data showed that there is a distinctive difference in glutamine metabolism between MYC and MET tumors. Our study has demonstrated the potential of [18F]FGln PET imaging as a tool to assess glutamine metabolism in HCC tumors in vivo with a caution that it may not be able to clearly distinguish HCC tumors from normal liver tissue.